GURU PAUD : PENDIDIKAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) ANAK USIA DINI - MARDHIATI, RETNO (Universitas Persada Indonesia YAI, 2019)
PHBS education in early childhood is very important. The children?s brains are growingrapidly at that time so that it will be easy to obtain PHBS education materials. However,materials specifically for PHBS early childhood education are not yet available. The purposeof this program was to provide education and skills to Early Childhood Education (ECD)teachers in presenting the material of PHBS for children in early childhood. This activity wasconducted in July 2015 at the District Office Kebayoran Baru, South Jakarta with 53 ECDteachers from districts Jagakarsa and Kebayoran Baru as participants. The material oneducation for early childhood PHBS include 8 themes, those are: washing hands with soap andwater flow, put garbage in the trash, exercise regularly, cutting the nails of hands and feet,brushing teeth after meals and before going to sleep, eating vegetables and fruit every day,choose clean and healthy snacks, and the using of sanitary latrines. The materials were gottenfrom brainstorming with ECD teachers on educational material needs PHBs early childhood.Continuous and well-planned effort to increase knowledge of early childhood health for ECDteachers must be made in the form of regular training activities as promotion and preventionhealth for children in early childhood.